Low-carbon ready-mixed mortar prepared from solid waste resources and preparation method of low-carbon ready-mixed mortar

By using solid waste-based gelling materials and modified fine nickel slag in the ready-mixed mortar, the problems of low utilization rate of solid waste resources and insufficient mortar performance are solved, and solid waste resources are efficiently utilized, and production costs are reduced. Improve the performance of mortar.

CN119462036APending Publication Date: 2025-02-18XIAMEN MEIYI GRP CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411541264.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the utilization rate of solid waste resources such as steel slag, nickel slag, and coal gangue is low, resulting in environmental pollution and resource waste. At the same time, the premixed mortar has shortcomings in strength, fluidity, water retention, etc.

Method used

By using solid waste-based gelling materials and modified fine nickel slag and other components, a low-carbon ready-mixed mortar is prepared, combining cement, fine aggregate, fiber filler and high-efficiency water reducer, optimize the ratio and process flow, and improve the The cementing ability and mechanical properties of the mortar.

Benefits of technology

It realizes the high added value utilization of solid waste resources, reduces the cost of mortar production, and improves the compressive strength, flexural strength, settling time and crack resistance of mortar, which is in line with the concept of energy conservation, emission reduction and green circulation development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112844490000051
    Figure BDA0005112844490000051
  • Figure BDA0005112844490000052
    Figure BDA0005112844490000052
  • Figure BDA0005112844490000053
    Figure BDA0005112844490000053
Patent Text Reader

Abstract

The invention relates to the technical field of building engineering materials, in particular to low-carbon ready-mixed mortar prepared from solid waste resources and a preparation method of the low-carbon ready-mixed mortar. The low-carbon premixed mortar prepared from the solid waste resources is prepared from the following preparation raw materials in parts by mass: 250 to 300 parts of cement, 300 to 400 parts of solid waste-based cementing material, 500 to 600 parts of fine aggregate, 8 to 12 parts of fiber filler, 8 to 12 parts of high-efficiency water reducing agent and 80 to 120 parts of water. The technical scheme provided by the invention not only has remarkable advantages in the aspects of environmental protection, resource conservation and economic benefits, but also has excellent performance in the aspects of improving mortar performance, prolonging service life and ensuring safety, and embodies technical innovation and sustainable development concepts in the field of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building engineering materials, and in particular to a low-carbon premixed mortar prepared from solid waste resources and a preparation method thereof. Background Art

[0002] my country's steel slag, nickel slag, coal gangue, stone chips and other wastes still have the problems of high production, large stock and low secondary utilization rate. At present, they are mostly treated by stacking or landfill, which causes great environmental pollution to the land and groundwater environment. In addition, the stability problem of refined slag used in building structures is also widely concerned. How to use such waste slag more efficiently has become an urgent problem to be solved.

[0003] With the development of science and technology, premixed mortar, as a new type of building material, green building material, and low-carbon material, has a lower emission rate of wastewater and waste gas in the production process, which meets the national requirements for the development of green building materials. At the same time, it shoulders the important mission of comprehensive utilization and recycling of industrial resources. According to statistics, the annual new construction area in my country is about 2 billion square meters, and the demand for building mortar should be 350-600 million tons. At present, the output of mortar is only 5% of the demand. Compared with premixed mortar, some commonly used special mortars such as wall and floor tile adhesives and interface treatment agents have industry standards, and their production and application are relatively mature. However, the commercialization process of premixed mortar is relatively slow. Most of the masonry and plastering mortars used on construction sites are still mixed on site, and the quality cannot be guaranteed, which is easy to have adverse effects on the construction quality and the surrounding environment. At present, the strength, fluidity, water retention, setting time, mechanical properties, and durability of premixed mortars need to be improved. Summary of the invention

[0004] The purpose of this application is to provide a low-carbon premixed mortar prepared from solid waste resources and a preparation method thereof in view of the deficiencies of current technologies. The low-carbon premixed mortar prepared from solid waste resources prepared in this application has the advantages of simple preparation, low cost, long service life, and green environmental protection, and has good compressive strength, flexural strength, setting time and crack resistance. It realizes the large-scale processing and high value-added utilization of solid waste resources such as steel slag, nickel slag, coal gangue and stone chips, and truly realizes energy conservation, emission reduction and green circular development in the resource process of steel slag, nickel slag, coal gangue and stone chips, which can effectively reduce the production cost of mortar and is beneficial to environmental protection.

[0005] In the first aspect, the present application provides a low-carbon premixed mortar prepared with solid waste resources, adopting the following technical scheme: a low-carbon premixed mortar prepared with solid waste resources, comprising the following preparation raw materials, measured by mass: 250-300 parts of cement, 300-400 parts of solid waste-based cementitious material, 500-600 parts of fine aggregate, 8-12 parts of fiber filler, 8-12 parts of high-efficiency water reducer, and 80-120 parts of water.

[0006] By adopting the above technical scheme, cement is used as the basic cementitious material of mortar to provide the basic bonding performance and structural strength of mortar. It works together with solid waste-based cementitious materials to improve the overall bonding ability and stability of mortar. Solid waste-based cementitious materials, cementitious materials made from industrial solid waste, reduce the production cost of mortar and reduce the environmental burden. After modification, the reaction activity is improved, and together with cement, it provides higher compressive strength and flexural strength; the addition of graphene accelerates the hydration reaction, generates more cementitious substances, and improves the performance of mortar. Fine aggregate provides the volume stability and hardness after molding required for mortar. It works together with other fillers to improve the workability and final mechanical properties of mortar. Fiber fillers enhance the compressive strength and flexural strength of mortar, and improve its toughness and crack resistance. The compatibility and photocatalytic ability of the modified treatment can further improve the comprehensive performance of concrete. High-efficiency water reducer reduces the amount of water required for mortar mixing, improves the fluidity and workability of mortar, and increases the density and strength of hardened mortar. Water adjusts the consistency of mortar to ensure that each component can fully react and mix. Working together with the water reducing agent, the optimal workability and hardening performance of the mortar are achieved. Through the precise proportion and interaction of these components, the low-carbon premixed mortar of the present application not only has excellent physical and chemical properties, but also realizes the high added value utilization of solid waste resources, which is in line with the concept of energy conservation, emission reduction and green circular development.

[0007] Preferably, the solid waste-based cementitious material is composed of steel slag, nickel slag and coal gangue in a mass ratio of 5:2:17-20 and is prepared by modification.

[0008] Preferably, the method for modifying the solid waste-based gelling material comprises the following steps: S31, according to the mass fractions, put 20 parts of calcium hydroxide, 30 parts of ammonium sulfate and 2 parts of graphene into a ball mill for ball milling at a ball milling speed of 30-40 r / min for a ball milling time of 5-8 min to obtain a mixture A; S32, according to the mass parts, put 200 parts of steel slag, 80 parts of nickel slag and 680-800 parts of coal gangue into a ball mill for ball milling at a ball milling speed of 30-40 r / min for a ball milling time of 5-8 min to obtain a mixture B; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 30-40r / min, and the ball milling time is 10-15min, to obtain a solid waste-based gelling material.

[0009] By adopting the above technical solution, steel slag: as an industrial byproduct, contains potential gelling components, which can undergo hydration reaction under certain conditions to form a hydration product with gelling properties. Nickel slag: also an industrial byproduct, can exert its potential gelling properties through appropriate treatment. Coal gangue: contains a certain amount of silicates and aluminates, which can form gelling substances under the action of activators. Ammonium sulfate: provides NH 4+ ions, which can promote the depolymerization of the glass and RO phases in steel slag and nickel slag, that is, destroy the Ca–O and Al–O bonds, thereby releasing Ca 2+ and Al 3+ ions. Calcium hydroxide: It can easily dissociate the agglomerates in the steel slag and continue to undergo hydration reaction to generate C–S–H (hydrated calcium silicate), which is beneficial to improving the activity of the steel slag. This is a key cementitious substance in the cement hardening process. Graphene: Adding graphene can promote the excitation reaction, accelerate the hydration reaction, and further generate more cementitious substances C–S–H. The high specific surface area and excellent conductivity of graphene may also improve the microstructure of the mortar, thereby improving its macroscopic performance. By solving the problem of steel slag stability, the safe use performance of steel slag is improved, the volume change of the mortar during the curing process is small, and the risk of cracking is reduced. The modified solid waste-based cementitious material provides better bonding in the mortar, and works together with cement to significantly improve the compressive strength and flexural strength of the mortar. The use of industrial solid waste to prepare cementitious materials reduces the disposal problem of these materials, while reducing the use of traditional cement, which is conducive to energy conservation, emission reduction and resource recycling. In general, through this modification treatment, solid waste-based cementitious materials are not only effectively utilized as resources, but also the overall performance of the mortar is improved, realizing the high-value application of waste, which is in line with the development direction of green building materials.

[0010] Preferably, the steel slag has a particle size of 0.5-1mm, accounting for 30-40% by mass, and a particle size of 2-5mm, accounting for 60-70% by mass; the coal gangue has a particle size of 2-6mm, accounting for 75-85% by mass, and a particle size of 0.5-1mm, accounting for 15-25% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm.

[0011] Preferably, the fine aggregate is composed of modified fine nickel slag and stone chips in a mass ratio of 1:7-9.

[0012] Preferably, the preparation method of the modified fine nickel slag is as follows: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 30-40 minutes to obtain the modified fine nickel slag.

[0013] By adopting the above technical scheme, the polyacrylic acid polymer improves the internal curing of the mortar through its excellent water absorption and water retention properties, which is beneficial to the moisture balance inside the mortar, thereby promoting the reaction of the fine nickel slag and improving the overall performance of the mortar. During the modification process, the interaction between the polyacrylic acid emulsion and the fine nickel slag enhances the interfacial strength between the filler and other components of the mortar, which helps to improve the compressive strength and flexural strength of the mortar. The use of polyacrylic acid polymer to modify fine nickel slag not only reduces the production cost of mortar, but also realizes the resource utilization of waste, which is in line with the development direction of green building materials. Through the above modification method, the role of fine nickel slag in the mortar has been significantly improved, which not only improves the physical properties of the mortar, but also promotes the high-value utilization of solid waste resources, achieving a win-win situation of economic and environmental benefits.

[0014] Preferably, the modified fine nickel slag is a continuously graded fine nickel slag with a particle size of 0.075mm-0.6mm; the particle size of the stone chips is not greater than 2.75mm, and the weight fraction of the stone powder in the stone chips is 8-10%.

[0015] Preferably, the preparation method of the fiber filler is to mix 100 parts of carbon fiber and 200 parts of pure water evenly, heat to 30-32°C, introduce ozone into the solution at a rate of 2-3L / min for 30-40min, and then stop the ozone supply; seal the solution, heat to 60-65°C, and let it stand for 3-4h; stir the solution in an open state for 20-30min, add 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5%, heat to 50°C and stir for 50min, then add 10-12 parts of titanium dioxide, stir for 20-30min, coat the titanium dioxide on the surface of the carbon fiber, filter, rinse with water 3 times, and vacuum dry at 80°C to obtain the fiber filler; the length of the carbon fiber is 3-5mm, and the particle size of the titanium dioxide is 80-120 nanometers.

[0016] By adopting the above technical scheme, the modified carbon fiber filler has good compatibility and photocatalytic ability, and can improve the compressive strength and flexural strength of concrete. Through the surface modification of 3-aminopropyltriethoxysilane and titanium dioxide, the interface strength between carbon fiber and other components of mortar is enhanced, and the overall performance of mortar is improved. The addition of titanium dioxide provides photocatalytic ability to carbon fiber, which may help improve the environmental tolerance of mortar, such as improving weather resistance or reducing the adsorption of harmful gases. Carbon fiber itself has high strength and toughness, and its distribution in mortar can effectively enhance the material's crack resistance. Through the above preparation method, the fiber filler not only exerts its own excellent performance in the mortar, but also further improves the compatibility and interaction with other components of the mortar through modification, thereby improving the mechanical properties of the mortar while also bringing it additional functional characteristics.

[0017] Preferably, the cement is ordinary Portland cement of grade P·O42.5; the high-efficiency water reducing agent is a polyhydroxy acid-based high-efficiency water reducing agent, and the water reducing rate is 30%.

[0018] In a second aspect, the present application provides a method for preparing low-carbon premixed mortar using solid waste resources, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned low-carbon premixed mortar prepared with solid waste resources, comprising the following steps: first, according to the mass proportions, mix cement, fiber filler, high-efficiency water reducer and water evenly, then add solid waste-based cementitious material and fine aggregate in sequence, stir evenly, and obtain low-carbon premixed mortar prepared with solid waste resources.

[0019] In summary, the beneficial technical effects of this application are: 1. Resource Utilization and Environmental Protection High value-added utilization of solid waste resources: By using industrial solid waste such as steel slag, nickel slag, and coal gangue as cementitious materials for mortar, large-scale processing and high value-added utilization of these materials are achieved, reducing the burden of industrial waste on the environment.

[0020] Energy saving and emission reduction: The application of solid waste-based cementitious materials reduces the use of traditional cement, which is conducive to reducing CO2 emissions and achieving green circular development.

[0021] 2. Performance Improvement Compressive strength and flexural strength: The use of modified fine nickel slag and other fillers improves the water absorption and water retention of the mortar, promotes chemical reactions, and enhances the compressive strength and flexural strength of the mortar.

[0022] Setting time and crack resistance: The doped and modified steel solid waste-based cementitious material has good compression resistance, flexural resistance and stability in the mortar, which significantly improves the setting time and crack resistance of the mortar.

[0023] 3. Economical cost reduction: Using solid waste resources as mortar raw materials effectively reduces the production cost of mortar, while reducing the cost of solid waste treatment and environmental governance costs.

[0024] 4. Technological innovation Application of composite materials: A composite material of calcium hydroxide, ammonium sulfate and graphene is used as an activator to improve the activity of steel slag and nickel slag, accelerate the hydration reaction, and generate more gelling substances C–S–H.

[0025] Carbon fiber filler modification: After modification, the carbon fiber filler not only improves the mechanical properties of the mortar, but also gives it good compatibility and photocatalytic ability.

[0026] 5. Service life and reliability Prolong service life: By improving the physical and chemical properties of the mortar, the stability and durability of the mortar during use are ensured, thereby extending its service life. DETAILED DESCRIPTION

[0027] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] In the following examples, preparation examples and comparative preparation examples, 1 part means 1 kg.

[0029] The main chemical components of nickel slag in the preparation examples and embodiments are shown in Table 1 below: Table 1 Main chemical composition of nickel slag The main chemical components of the coal gangue in the preparation examples and embodiments are shown in Table 2 below: Table 2 Main chemical components of coal gangue The main chemical components of the steel slag in the preparation examples and embodiments are shown in Table 3 below: Table 3 Main chemical composition of steel slag Preparation Example 1 The method for modifying solid waste-based cementitious materials comprises the following steps: S31, according to the mass parts, put 20 parts of calcium hydroxide, 30 parts of ammonium sulfate and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 30r / min, the ball milling time is 5min, and a mixture A is obtained; S32, according to the mass fractions, 200 parts of steel slag, 80 parts of nickel slag and 680 parts of coal gangue are put into a ball mill for ball milling treatment, the ball milling speed is 30r / min, the ball milling time is 8min, and a mixture B is obtained, wherein the particle size of the steel slag is 0.5-1mm, accounting for 30% by mass, and the particle size is 2-5mm, accounting for 70% by mass; the particle size of the coal gangue is 2-6mm, accounting for 75% by mass, and the particle size is 0.5-1mm, accounting for 25% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 30r / min, and the ball milling time is 15min, to obtain a solid waste-based gelling material.

[0030] Preparation Example 2 The method for modifying solid waste-based cementitious materials comprises the following steps: S31, according to the mass parts, put 20 parts of calcium hydroxide, 30 parts of ammonium sulfate and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 40r / min, the ball milling time is 5min, and a mixture A is obtained; S32, according to the mass fractions, 200 parts of steel slag, 80 parts of nickel slag and 800 parts of coal gangue are put into a ball mill for ball milling treatment, the ball milling speed is 40r / min, and the ball milling time is 5min, to obtain a mixture B, wherein the steel slag has a particle size of 0.5-1mm accounting for 40% by mass, and a particle size of 2-5mm accounting for 60% by mass; the coal gangue has a particle size of 2-6mm accounting for 85% by mass, and a particle size of 0.5-1mm accounting for 15% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 40r / min, and the ball milling time is 10min, to obtain a solid waste-based gelling material.

[0031] Preparation Example 3 The method for modifying solid waste-based cementitious materials comprises the following steps: S31, according to the mass parts, put 20 parts of calcium hydroxide, 30 parts of ammonium sulfate and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 35r / min, the ball milling time is 7min, and a mixture A is obtained; S32, according to the mass fractions, 200 parts of steel slag, 80 parts of nickel slag and 750 parts of coal gangue are put into a ball mill for ball milling treatment, the ball milling speed is 35r / min, the ball milling time is 7min, and a mixture B is obtained, wherein the particle size of the steel slag is 0.5-1mm, accounting for 35% by mass, and the particle size is 2-5mm, accounting for 65% by mass; the particle size of the coal gangue is 2-6mm, accounting for 80% by mass, and the particle size is 0.5-1mm, accounting for 20% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 35r / min, the ball milling time is 13min, and a solid waste-based gelling material is obtained.

[0032] Preparation Example 4 Preparation of Fiber Filler The preparation method of the fiber filler is as follows: 100 parts of carbon fiber and 200 parts of pure water are mixed evenly, the temperature is raised to 31°C, ozone is introduced into the solution at a rate of 2.5L / min for 35 minutes, and then the ozone supply is stopped; the solution is sealed, heated to 62°C, and allowed to stand for 4 hours; the solution is stirred for 30 minutes in an open state, 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5% are added, heated to 50°C and stirred for 50 minutes, and then 11 parts of titanium dioxide are added, stirred for 25 minutes, the titanium dioxide is coated on the surface of the carbon fiber, filtered, rinsed with water 3 times, and vacuum dried at 80°C to obtain the fiber filler; the length of the carbon fiber is 3-5mm, and the average particle size of the titanium dioxide particles is 90 nanometers.

[0033] Preparation Example 5 Preparation of modified fine nickel slag The preparation method of modified fine nickel slag is as follows: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 35 minutes. The modified fine nickel slag is a continuously graded fine nickel slag with a particle size of 0.075mm-0.6mm, so as to obtain modified fine nickel slag.

[0034] Preparation Comparative Example 1 The method for preparing a solid waste-based gelling material comprises the following steps: S32. According to the mass fractions, 200 parts of steel slag, 80 parts of nickel slag and 750 parts of coal gangue are put into a ball mill for ball milling treatment. The ball milling speed is 35r / min and the ball milling time is 7min to obtain a solid waste-based cementitious material. The particle size of the steel slag is 0.5-1mm, accounting for 35% by mass, and the particle size is 2-5mm, accounting for 65% by mass; the particle size of the coal gangue is 2-6mm, accounting for 80% by mass, and the particle size is 0.5-1mm, accounting for 20% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm; Example 1 A low-carbon premixed mortar prepared from solid waste resources, comprising the following raw materials by weight: 250 parts of cement, 300 parts of solid waste-based cementitious materials, 500 parts of fine aggregate, 8 parts of fiber filler, 8 parts of high-efficiency water reducer, and 80 parts of water, wherein the solid waste-based cementitious materials are the solid waste-based cementitious materials prepared in Preparation Example 1, the fine aggregate is composed of modified fine nickel slag and stone chips (with a particle size of not more than 2.75 mm, and the weight fraction of stone powder in the stone chips is 8%) in a mass ratio of 1:7, the cement is P·O42.5 grade ordinary Portland cement; the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer, and the water reduction rate is 30%; The above-mentioned method for preparing low-carbon premixed mortar prepared with solid waste resources includes the following steps: first, according to the mass proportions, mix cement, fiber filler, high-efficiency water reducer and water evenly, then add solid waste-based cementitious material and fine aggregate in sequence, stir evenly, and obtain low-carbon premixed mortar prepared with solid waste resources.

[0035] Example 2 A low-carbon premixed mortar prepared from solid waste resources, comprising the following raw materials by weight: 300 parts of cement, 400 parts of solid waste-based cementitious materials, 600 parts of fine aggregate, 12 parts of fiber filler, 12 parts of high-efficiency water reducer, and 120 parts of water, wherein the solid waste-based cementitious materials are the solid waste-based cementitious materials prepared in Preparation Example 2, the fine aggregate is composed of modified fine nickel slag and stone chips (with a particle size of not more than 2.75 mm, and the weight fraction of stone powder in the stone chips is 10%) in a mass ratio of 1:9, the cement is P·O42.5 grade ordinary Portland cement; the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer, and the water reduction rate is 30%; The above-mentioned method for preparing low-carbon premixed mortar prepared with solid waste resources includes the following steps: first, according to the mass proportions, mix cement, fiber filler, high-efficiency water reducer and water evenly, then add solid waste-based cementitious material and fine aggregate in sequence, stir evenly, and obtain low-carbon premixed mortar prepared with solid waste resources.

[0036] Example 3 A low-carbon premixed mortar prepared from solid waste resources, comprising the following raw materials by weight: 280 parts of cement, 350 parts of solid waste-based cementitious materials, 550 parts of fine aggregate, 10 parts of fiber filler, 10 parts of high-efficiency water reducer, and 100 parts of water, wherein the solid waste-based cementitious materials are the solid waste-based cementitious materials prepared in Preparation Example 3, the fine aggregate is composed of modified fine nickel slag and stone chips (with a particle size of not more than 2.75 mm, and the weight fraction of stone powder in the stone chips is 9%) in a mass ratio of 1:8, the cement is P·O42.5 grade ordinary Portland cement; the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer, and the water reduction rate is 30%; The above-mentioned method for preparing low-carbon premixed mortar prepared with solid waste resources includes the following steps: first, according to the mass proportions, mix cement, fiber filler, high-efficiency water reducer and water evenly, then add solid waste-based cementitious material and fine aggregate in sequence, stir evenly, and obtain low-carbon premixed mortar prepared with solid waste resources.

[0037] Comparative Example 1 The same as Example 3, except that an equal amount of the solid waste-based cementitious material prepared in Preparation Comparative Example 1 is used instead of the solid waste-based cementitious material prepared in Preparation Example 3.

[0038] Comparative Example 2 Same as Example 3, except that an equal amount of unmodified carbon fibers (length 3-5 mm) are used instead of the fiber filler.

[0039] Comparative Example 3 The same as Example 3, except that an equal amount of unmodified fine nickel slag (continuously graded fine nickel slag with a particle size of 0.075 mm-0.6 mm) is used instead of the modified fine nickel slag.

[0040] Performance Testing The low-carbon premixed mortar prepared with solid waste resources obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was made into test pieces. The test pieces were cubes with a side length of 100 mm. The surfaces were sealed with polyethylene film and cured at room temperature for 24 hours before demolding. The mortars were moved to a standard curing box and cured to the corresponding age. The following tests were performed. The test results are shown in Table 4.

[0041] The mechanical properties are tested according to the national standard GB / T17671-2021 after the specimens are cured for 28 days; Stability: Tested according to the Leclerc clamp test standard in GB / T1346-2011; The water retention rate and consistency are tested in accordance with the national standard GB / T25181-2019 for premixed mortar and the standard JGJ / T70-2009 for basic performance test methods for building mortar; Shrinkage performance: After the specimens are cured for 28 days, they are tested in accordance with JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar".

[0042] Table 4 Performance test Analyzing the data in Table 4, we can see that: 1) The low-carbon premixed mortar prepared from solid waste resources obtained in Examples 1 to 3 has good compressive strength, flexural strength, setting time and crack resistance. It realizes large-scale processing and high value-added utilization of solid waste resources such as steel slag, nickel slag, coal gangue and stone chips, truly realizes energy conservation, emission reduction and green circular development in the resource process of steel slag, nickel slag, coal gangue and stone chips, can effectively reduce the production cost of mortar and is beneficial to environmental protection.

[0043] 2) The comparative analysis of the performance of the low-carbon premixed mortar prepared with solid waste resources obtained in Example 3 and Comparative Example 1 shows that by modifying the solid waste-based cementitious materials, the modified solid waste-based cementitious materials provide better bonding in the mortar, and work together with cement to significantly improve the compressive strength and flexural strength of the mortar. The use of industrial solid waste to prepare cementitious materials reduces the disposal problems of these materials, while reducing the use of traditional cement, which is conducive to energy conservation, emission reduction and resource recycling. In general, through this modification treatment, the solid waste-based cementitious materials are not only effectively utilized as resources, but also improve the overall performance of the mortar, realize the high-value application of waste, and are in line with the development direction of green building materials.

[0044] 3) The performance comparison analysis of the low-carbon premixed mortar prepared with solid waste resources obtained in combination with Example 3 and Comparative Example 2 shows that the polyacrylic acid polymer improves the internal curing of the mortar through its excellent water absorption and water retention properties, which is beneficial to the moisture balance inside the mortar, thereby promoting the reaction of the fine nickel slag and improving the overall performance of the mortar. During the modification process, the interaction between the polyacrylic acid emulsion and the fine nickel slag enhances the interfacial strength between the filler and other components of the mortar, which helps to improve the compressive strength and flexural strength of the mortar. The use of polyacrylic acid polymer to modify the fine nickel slag not only reduces the production cost of the mortar, but also realizes the resource utilization of waste, which is in line with the development direction of green building materials. Through the above-mentioned modification method, the role of fine nickel slag in the mortar has been significantly improved, which not only improves the physical properties of the mortar, but also promotes the high-value utilization of solid waste resources, achieving a win-win situation of economic benefits and environmental benefits.

[0045] 4) The performance comparison analysis of the low-carbon premixed mortar prepared with solid waste resources obtained in combination with Example 3 and Comparative Example 3 shows that the modified carbon fiber filler has good compatibility and photocatalytic ability, and can improve the compressive strength and flexural strength of concrete. The surface modification of 3-aminopropyltriethoxysilane and titanium dioxide enhances the interfacial strength between the carbon fiber and other components of the mortar, and improves the overall performance of the mortar. The addition of titanium dioxide provides carbon fiber with photocatalytic ability, which may help improve the environmental tolerance of the mortar, such as improving weather resistance or reducing the adsorption of harmful gases. Carbon fiber itself has high strength and toughness, and its distribution in the mortar can effectively enhance the material's crack resistance.

[0046] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A low-carbon premixed mortar prepared from solid waste resources, characterized in that: The preparation raw materials include the following by mass: 250-300 parts of cement, 300-400 parts of solid waste-based cementitious materials, 500-600 parts of fine aggregate, 8-12 parts of fiber filler, 8-12 parts of high-efficiency water reducing agent, and 80-120 parts of water.

2. A low-carbon premixed mortar prepared from solid waste resources according to claim 1, characterized in that: The solid waste-based cementitious material is composed of steel slag, nickel slag and coal gangue in a mass ratio of 5:2:17-20 and is prepared by modification.

3. A low-carbon premixed mortar prepared from solid waste resources according to claim 2, characterized in that: The method for modifying solid waste-based gelling materials comprises the following steps: S31, according to the mass parts, put 20 parts of calcium hydroxide, 30 parts of ammonium sulfate and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 30-40r / min, the ball milling time is 5-8min, and a mixture A is obtained; S32, according to the mass parts, put 200 parts of steel slag, 80 parts of nickel slag and 680-800 parts of coal gangue into a ball mill for ball milling at a ball milling speed of 30-40 r / min for a ball milling time of 5-8 min to obtain a mixture B; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 30-40r / min, and the ball milling time is 10-15min, to obtain a solid waste-based gelling material.

4. The low-carbon premixed mortar prepared from solid waste resources according to claim 2, characterized in that: The steel slag has a particle size of 0.5-1mm, accounting for 30-40% by mass, and a particle size of 2-5mm, accounting for 60-70% by mass; the coal gangue has a particle size of 2-6mm, accounting for 75-85% by mass, and a particle size of 0.5-1mm, accounting for 15-25% by mass; the nickel slag is a continuously graded nickel slag with a particle size of 0.5mm-4.75mm.

5. The low-carbon premixed mortar prepared from solid waste resources according to claim 1, characterized in that: The fine aggregate is composed of modified fine nickel slag and stone chips in a mass ratio of 1:7-9.

6. The low-carbon premixed mortar prepared from solid waste resources according to claim 5, characterized in that: The preparation method of the modified fine nickel slag is as follows: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 30-40 minutes to obtain the modified fine nickel slag.

7. The low-carbon premixed mortar prepared from solid waste resources according to claim 5, characterized in that: The modified fine nickel slag is a continuously graded fine nickel slag with a particle size of 0.075mm-0.6mm; the particle size of the stone chips is not greater than 2.75mm, and the weight fraction of the stone powder in the stone chips is 8-10%.

8. The low-carbon premixed mortar prepared from solid waste resources according to claim 1, characterized in that: The preparation method of the fiber filler is as follows: 100 parts of carbon fiber and 200 parts of pure water are mixed evenly, the temperature is raised to 30-32°C, ozone is introduced into the solution at a speed of 2-3L / min for 30-40min, and then the ozone supply is stopped; the solution is sealed, heated to 60-65°C, and allowed to stand for 3-4h; the solution is stirred for 20-30min in an open state, 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5% are added, the solution is heated to 50°C and stirred for 50min, and then 10-12 parts of titanium dioxide are added, stirred for 20-30min, the titanium dioxide is coated on the surface of the carbon fiber, filtered, rinsed with water 3 times, and vacuum dried at 80°C to obtain the fiber filler; the length of the carbon fiber is 3-5mm, and the particle size of the titanium dioxide is 80-120 nanometers.

9. The low-carbon premixed mortar prepared from solid waste resources according to claim 1, characterized in that: The cement is ordinary Portland cement of grade P·O42.5; the high-efficiency water reducing agent is a polyhydroxy acid-based high-efficiency water reducing agent with a water reduction rate of 30%.

10. A method for preparing a low-carbon premixed mortar prepared from solid waste resources according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the mass proportions, cement, fiber filler, high-efficiency water reducing agent and water are first mixed evenly, and then solid waste-based cementitious materials and fine aggregate are added in sequence and stirred evenly to obtain low-carbon premixed mortar prepared with solid waste resources.

Citation Information

Cited By

  • Low-carbon environment-friendly seawater corrosion-resistant mortar and preparation method thereof

    CN120025134A

  • Cold casting molding clay sculpture material based on solid waste and preparation method of cold casting molding clay sculpture material

    CN122380718A